Weather Risk and the World Food Program. - Mazzotta, Benjamin. (2017)
Abstract: Weather risk management is a set of financial products including insurance, catastrophe bonds, and derivative contracts based on seasonal precipitation and temperature. International organizations have recently put their toes in the water to see whether insurance and weather derivatives can help them secure conditional access to necessary funds for predictable emergencies. Ethiopia is the epicenter of financial innovation for food security, first in the form of a pilot weather insurance program at World Food Program, and subsequently with a risk financing program in the Productive Safety Nets Program. Why did these organizations innovate in this way? Financial theory predicts that firms optimize a portfolio of hedged and unhedged cash flows to protect the organization from risk. Rational choice predicts that firms seek the greatest possible access to funds while preserving the greatest latitude for operational independence. I show that the safety net program seeks to improve foresight and transparency over its program objectives, rather than credibility with international creditors or even operational partners in the field. I analyze the decisions made by WFP and PSNP related to financial risk management, using process tracing and grounded theory. Applications of the research include contract design for international humanitarian assistance, and potentially a market opportunity for financial services in the international public sector.; Thesis (Ph.D.)--Tufts University, 2011.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: Daniel Drezner.; Committee: Jenny Aker, and Patrick Webb.; Keyword: International Relations.